Opportunities for Microbiome Suppression of Weeds Using Regenerative Agricultural Technologies - Cheng, Liang; DiTommaso, Antonio; Kao-Kniffin, Jenny (Frontiers in Soil Science, 2022)
The goal of regenerative agriculture is to utilize technologies that build healthy soils and improve the environment. Microbial technologies could play a significant role in reducing reliance on synthetic herbicides for weed control. In the United States, the expenditure on herbicides exceeds $5 billion annually and accounts for 58% of the total pesticide use nationally. This overreliance on chemical weed control has exacerbated herbicide resistance in a multitude of weed species, leading to aggressive cultivation practices that contribute to soil erosion and depletion. The proliferation of microbiome research in agriculture has increased our understanding of the complex interactions between plant species and their microbiota. Microbial technologies offer novel weed management strategies that could reduce the need for herbicides. Some of these strategies could also help rebuild soil and improve environmental quality. Specifically, we propose three emerging areas in microbiome science that can enhance weed management: 1) identifying soil microorganisms that inhibit weed growth; 2) discovering microbial natural products that suppress weeds; and 3) developing field management approaches that promote weed suppression by enhancing soil microbiome function.